IMPROVING SPEAKING THROUGH INSIDE AND OUTSIDE CIRCLE STRATEGY - Ni Putu Yuliastuti; Dewa Gede Agung Gana Kumara; Ni Wayan Krismayani (Jurnal Santiaji Pendidikan (JSP), 2024)
This research used a classroom action research design conducted at SMPN 2 Ubud, Bali. The pre-test results showed that students needed help with fluency, comprehensiveness, and grammar speaking skills. In addition, this research aimed to determine whether seventh-grade students' speaking skills could be improved by implementing the Inside and Outside Circle strategy. The research was carried out in two cycles, with two sessions. Tests and questionnaires served as the research instruments. Fifty-eight were the results of the pre-test, while 69 and 79 were the post-test I and II findings. After that, the data was examined by contrasting the pre-test and post-test results, which led to a notable increase in the individuals' mean scores. Questionnaires were distributed as supplementary data after the previous cycle. The individuals' positive reactions to the strategy's implementation were evident from the questionnaire's results. According to the results of the research instrument, the inside and outside circle strategy can improve students' speaking abilities.